An Assessment of Residents’ Housing Satisfaction and Coping in Accra, Ghana - Baiden, P.; Arku, G.; Luginaah, I.; Asiedu, A.B. (Springer, 2011)
Aim: The present paper is an original research that explores housing satisfaction and residents’ ability to cope with day-to-day demands, taking into account other dimensions of housing and socio-demographic factors. Subjects and methods: A cross-sectional survey (n=562) was randomly administered to residents in three neighbour-hoods (Labone, Asylum Down and Nima) in Accra, Ghana. The association between the outcome variables and housing attributes were analysed using logistic regression. Results: The findings indicate that housing satisfaction was significantly predicted by age, with older people more likely to be dissatisfied with their housing arrangement. Respondents were dissatisfied with housing arrangements if they lived in Nima [odds ratio (OR) =2.75, p<.001], Asylum Down (OR=1.72, p<.01), crowded households (OR=1.158, p<.05) or in compound houses (OR=2.50, p<.001). In the context of housing attribute variables, respondent’s ability to cope with day-to-day demands was significantly associated to their income level. Odour annoyance as an indicator of housing condition emerged as a strong predictor of respondent’s inability to cope with daily demands with OR ranging from 1.68 to 2.33. Those who were dissatisfied with the location of their home as a place to live also reported poor coping abilities (OR=1.86, p<.01). Discussion and conclusions: From the findings, government policy on housing should encourage the construction of more affordable housing units to ease the crowding situation in Accra. There is also a need for the Accra City Council to provide clearer guidelines for both tenants and landlords in response to increasing tenancy disputes in context.
Keywords: Housing; Health; Housing satisfaction; Coping; Accra